Minimally Invasive Urology 2014
DOI: 10.1007/978-1-4939-1317-6_5
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Radical Prostatectomy

Abstract: In the field of oncologic urologic surgery, robot-assisted radical prostatectomy (RARP) represents the main application of the robotic approach. RARP is currently the leading urologic use of the da Vinci system, and more than 80 % of the radical prostatectomies performed in the USA in 2011 were carried out by robot-assisted surgery. Indications for RARP are the same with those for radical retropubic prostatectomy (RRP), and RARP has also been described as a salvage surgical treatment after radiotherapy (RT), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…After screening, 8 studies met the inclusion criteria to evaluate the efficacy and safety of SP and MP surgery (37)(38)(39)(40). The meta-analysis of these studies showed that there were differences in operation time, and the time of SP robot-assisted surgery was shorter than that of MP robotassisted surgery (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…After screening, 8 studies met the inclusion criteria to evaluate the efficacy and safety of SP and MP surgery (37)(38)(39)(40). The meta-analysis of these studies showed that there were differences in operation time, and the time of SP robot-assisted surgery was shorter than that of MP robotassisted surgery (41,42).…”
Section: Discussionmentioning
confidence: 99%